Flexible discretely-magnetized configurable soft robots via laser-tuned selective transfer printing of anisotropic ferromagnetic cells. (March 2021) - Ke, X.; Zhang, S.; Chai, Z.; Jiang, J.; Xu, Y.; Tao, B.; Ding, H.; Wu, Z.
Abstract: Meso- or micro-scale soft robots with specific magnetization profiles have been demonstrated advanced locomotion capabilities in a plethora of unstructured environments. Despite some earlier success, technical challenges still exist for flexibly fabricating sophisticated constructed, heterogeneous and configurable soft magnetic robots at a relatively low cost. Here, by developing a new selective surface adhesion tuning, we report a transfer printing-based approach to flexibly configure magnetic domains for making 2/3-dimensional (2/3D) shaped fast-transforming untethered soft magnetic robots as well as heterogeneous integration of other desirable functional cells. This method enables physical realization of modular configurable magnetic robots integrated with specific magnetized profiles and other functional units like LEGO's strategy. Further, we demonstrate a series of magnetic robots capable of configurable motion and responsive behaviors. This technique can serve as a new platform technique, potentially broadening the physical realization of heterogeneous integrable soft magnetic robots and empowering them with new capabilities and possibilities. Graphical abstract: Image 1 Highlights: Selective surface adhesion tuning via laser surficial morphology alteration. Selective transfer printing technique leveraging laser selective adhesion tuning. A LEGO's strategy to flexibly configure heterogeneous soft magnetic robots. This method isuseful for the integration and synergy of multifunctionalities for higher intelligent soft robots.